Chemical characterization of medium-chain-length polyhydroxyalkanoates (PHAs) recovered by enzymatic treatment and ultrafiltration - Kathiraser, Y.; Aroua, M.K.; Ramachandran, K.B.; Tan, I.K.P. (2007)
BACKGROUND: Medium-chain-length polyhydroxyalkanoates (PHAs) are biodegradable polyesters accumulated intracellularly as energy resources by bacterial species such as Pseudomonas putida. The most popular method for PHA recovery is solvent extraction using trichloromethane (chloroform) and methyl alcohol (methanol). An alternative method is enzymatic treatment, which eliminates usage of these hazardous solvents. This research focuses on the characterization of PHAs recovered by enzymatic treatments and ultrafiltration. Comparisons are made with conventional solvent extracted PHA. RESULTS: The purity of PHA in water suspension recovered by enzymatic treatments as analyzed by gas chromatography was 92.6. Enzymatically recovered PHA was comparable to conventional solvent-extracted PHA, which had a purity of 95.5. PHA was further characterized for functional group analysis, structural composition analysis and molecular weight determination. It was found that the molecular weight of the PHA recovered by enzymatic treatment was less than solvent-extracted PHA, probably due to degradation of the lipopolysaccharide layer. However, functional group and structural composition analyses showed similar results for PHA recovered by both methods. CONCLUSION: PHAs recovered through enzymatic digestion treatment have good comparability with solvent-extracted PHAs. Thus enzymatic digestion has great potential as an alternative recovery method. (C) 2007 Society of Chemical Industry.